Benefits and barriers to women's participation in ecotourism development within the Kakum Conservation Area (Ghana): Implications for community planning. Issue 5 (19th October 2020) - Nutsugbodo, Ricky Yao; Adjei Mensah, Collins
ABSTRACT: Women's participation in community development projects is now essential as it helps to promote inclusive development and decentralized development planning. This paper assesses the perceived benefits and barriers to women's participation in ecotourism development and their implications for community planning at the Kakum Conservation Area (KCA). Using questionnaires, a total of 169 women from four selected communities within the KCA were sampled through a cluster sampling technique. The women were found to have perceived that the KCA project has yielded more environmental benefits than socio-cultural and economic benefits. They were uncertain as to whether the constraints inhibiting their participation were cultural or personal but were certain on operational and structural barriers. To address the situation, the Ghana Tourism Authority and the District Assemblies in the area should ensure the proper functioning of the decentralized planning structures for women to participate well and obtain the necessary benefits therein.